Implementation of Braille-Mobile Device to Help Visually and Speech-Impaired Persons Communicate Based on the Blynk IoT - Kamaruddin, Kamaruddin; Suparno, I Wayan; Jalil, Abdul; Fauzy, Ahmad; Serlina, Serlina (Politeknik Negeri Batam, 2025)
Visual and speech impairment is a condition in which an individual is unable to communicate with family or society due to the inability to see and speak. The objective of this study is to develop a Braille-Mobile device that assists individuals with visual and speech disabilities in communicating remotely with family members or society using Internet of Things (IoT) technology. In this study, the method used to generate messages from the Braille-Mobile device is based on the combination of six buttons pressed on the device, which are translated into letters using the Braille code concept. The messages are then transmitted via the Blynk IoT platform from the Braille-Mobile device to the mobile devices of family members or society through the Internet network. The results of this study show that the developed Braille-Mobile device can be used to send messages in the form of the words HELP, EAT, DRINK, and DRUG to family smartphones using IoT technology with a success rate of up to 76.25% and a message transmission time ranging from 4 to 8 seconds. Furthermore, the Braille-Mobile device is also capable of receiving confirmation from family smartphones in the form of voice responses.